Marks' basic medical biochemistry : A clinical approach - Lieberman, Michael, 1950-; Peet, Alisa (Philadelphia : Wolters Kluwer Health, 2022)
"It has been 5 years since the fifth edition was completed. The sixth edition has some significant organizational changes, as suggested by extensive surveys of faculty and students who used the fifth edition in their classes and studies"--
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Biochemical Phenomena; Clinical Medicine